The Effect of Implementation of Inquiry-based Learning with Socio-scientific Issues on Students' Higher-Order Thinking Skills - Sitti Nurul Qamariyah; Sri Rahayu; Fauziatul Fajaroh; Naif Mastoor Alsulami (Universitas Pendidikan Indonesia, 2021)
This study investigates the effect of inquiry-based learning with socio-scientific issues on students' higher-order thinking skills in the first year based on chemistry topics. This study used a quasi-experiment design as a method. A sample of 96 students in three classes was selected and was divided into two groups. An experimental group used two classes (68 students) that received the instruction by inquiry-based learning with socio-scientific issues, while the control group (28 students) received instruction using verification learning. The data were collected using pretest and post-test. The results were analyzed using SPSS 16.0 for windows software by employing ANOVA and effect size. This study showed that the experimental groups have a higher score in Higher Order Thinking Skills than the control group students, and there was a significant difference between the experimental groups and the control group with a large effect size. Thus, this study concluded that inquiry-based learning with socio-scientific issues helps conduct the classroom's learning strategies to improve students' higher-order thinking skills.